Citizenship Without Inclusion: Examining the Experiences of University Students with Disabilities in Pakistan's Higher Education System - Dr Yaar Muhammad,; Dr Amna Yousaf,; Dr Sajid Masood, (Dialogue Social Science Review (DSSR), 2025)
In this qualitative study, the authors employ the critical realist approach to elucidate the lived experiences of higher education students with disabilities within the Pakistani system of higher education. As it is in the Pakistani constitution, the rights of citizenship and access to everything, at least formally, are guaranteed; students with disabilities face the paradox of formal citizenship that comes together with significantly low substantive inclusion because of systematic exclusion. The conflict between the policy rhetoric on which the constituent provisions of the constitution are based, on the one hand, and the practices of daily exclusion of students with various disabilities, on the other, is quite brightly reflected in the results of 20 in-depth interviews with a sample of students in three large Pakistani universities who have different disabilities. The paper also scrutinizes the role that institutional structures, cultural norms, and resource limitations play in marginalizing these students, thus pushing them to the edge of university life. The results indicate that the students receive a form of citizenship without any inclusion, although they are citizens in terms of status and have a right to education (because of this legal provision). Poor infrastructure, discriminatory faculty and peer attitudes, a lack of support services, and the failure to engage in mainstream campus activities constitute the significant dimensions of this exclusion. The study employs critical realist epistemology to inform a thematic analysis that identifies structural mechanisms maintaining exclusion, while also highlighting the concept of student agency and the methods of resistance. The findings challenge hegemonic trends in inclusion within the context of Pakistani higher education and promote radical solutions that extend beyond compliance to achieve actual accessibility and a sense of belonging.